Comparison of step characteristic interaction and asymmetry between failed and succesful attempts in pole vault - Theodorou, A.; Panoutsakopoulos, V.; Exell, T.; Vujkov, N. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate step characteristics of high level pole vaulters during failed and successful jumps in terms of: a) the direction and magnitude of asymmetry between the pole carrying (PC) and non-pole carrying (NPC) foot and b) the reliance of step velocity (SV) on either step frequency (SF) or step length (SL). Eight male pole vaulters were recorded during competition with a panning video camera operating at 300 fps. Asymmetry was observed in four vaulters on either SF or SL both in successful and failed attempts but it was not consistent and its direction was not related to the athletes` PC limb. No athletes demonstrated significant asymmetry for SV between failed and successful jumps. At the highest jump cleared, five out of eight vaulters demonstrated SF reliance. However, as the failed attempts progressed vaulters became less SF reliant.